Peran Manajemen Komunikasi Krisis terhadap Kebangkrutan PT. Sepatu Bata TBK - Fina Abiyya Agustin Mubarokah; Hawa Arofah Qusdy; Nur Hamidah; Chalifa Al Firza; Lilik Sumarni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the bankruptcy crisis communication of PT. Sepatu Bata tbk, using the literature review research method to collect data through several journals and articles. The bankruptcy of PT Bata is a significant case of business failure and shows the tight competition between industries. This study analyzes the factors causing the bankruptcy of PT Bata, namely: changes in consumer behavior, inability to face competition, business strategy errors, and declining economic conditions. The results of the study indicate that the bankruptcy of PT Bata has an impact on decreasing stock values, reducing the workforce, and losses for creditors. This study contributes to the understanding of the factors causing corporate bankruptcy and the importance of strategic planning. As well as for future improvements.